The effect of chem-preneurship-based project learning on students' creativity - Prayitno, Mohammad Agus; Solikhah, Mar'attus; Khamidah, Nur (Research and Social Study Institute, 2024)
21st-century education not only involves aspects of knowledge but also emphasizes aspects of skills, such as critical thinking skills, creative thinking skills, communication, and collaboration. Creative thinking skills can be developed through contextual learning activities. One type of contextual learning is Chem-preneurship-based Project Learning (CBPL). CBPL trains students to be able to creatively design ideas, make products, design packaging, and do marketing. This study aimed to determine the effectiveness of the CBPL model. The research method used is descriptive quantitative. The population in this study were students of the 3rd semester of the department of chemistry. The sample of this study was 37 students who took Chem-partnership courses. The data analysis used is non-parametric statistical analysis. The results of the Wilcoxon test on student creativity obtained sig < 0.05, which means there were differences in student creativity before and after CBPL learning was implemented. The average score of students' creativity has increased from 58.83 to 82.34.